2004
DOI: 10.1079/phn2003511
|View full text |Cite
|
Sign up to set email alerts
|

Having lunch at a staff canteen is associated with recommended food habits

Abstract: Having lunch at staff canteens is associated with the quality of the diet. To serve a cooked meal including vegetables during working time may be an efficient way to improve diet among adult employees. More emphasis should be put on increasing the possibility for employees to have lunch at staff canteens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
101
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 16 publications
12
101
1
3
Order By: Relevance
“…This study confirmed that education is strongly associated with workplace cafeteria use, a result which has also been found in earlier studies 4,10 . The association between education and the use of a workplace cafeteria could be partly explained by working conditions, since well-educated people are more likely to work at places where the cafeterias are arranged properly and they may also have better financial resources for eating at the cafeterias.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirmed that education is strongly associated with workplace cafeteria use, a result which has also been found in earlier studies 4,10 . The association between education and the use of a workplace cafeteria could be partly explained by working conditions, since well-educated people are more likely to work at places where the cafeterias are arranged properly and they may also have better financial resources for eating at the cafeterias.…”
Section: Discussionsupporting
confidence: 92%
“…Employees' food choices at workplace cafeterias are indeed found to be more in line with nutritional recommendations than at other eating places, since, for instance, fresh vegetables, vegetarian foods and fish are favoured [9][10][11] .…”
mentioning
confidence: 99%
“…In Finland, as well as elsewhere, following the recommended food habits tends to be more common among individuals in higher socio-economic positions (10)(11)(12)(13) ; however, this is not completely consistent for all food habits (14) . Thus, people in higher socio-economic groups consume less traditional foods such as dark rye bread (15) , but more fresh vegetables (16) .…”
mentioning
confidence: 99%
“…With this classification, healthy food habits were followed by 28% of women and 17% of men. A similar index has also been used in previous studies Roos et al, 2004). Only those who responded to the food frequency inventory were included in the analyses.…”
Section: Healthy Food Habitsmentioning
confidence: 99%